Waste glass as a substitution for binder and sand in concrete: mechanical and physical properties - Gholampour, Aliakbar; Ozbakkaloglu, Togay; Kiamahalleh, Mohammad Valizadeh; Gençel, Osman; Gençel, Osman (Springer Int Publ Ag, 2025)
Replacing cement with glass powder (GP) and natural sand with glass sand (GS) in concrete could provide a compelling pathway to a sustainable construction to reduce environmental impacts of both concrete and waste glass. An experimental investigation on concrete, where cement is substituted by GP, fly ash (FA), and ground granulated blast furnace slag (GGBS) and natural sand is substituted by GS, is presented. 17 mixes were considered, and workability, density, elastic modulus, compressive strength, and water absorption were evaluated. Results indicate that the GP particle size significantly affects the concrete properties. Increasing the GP particle size decreases the concrete compressive strength and elastic modulus. The replacement of cement with GGBS at a 55% level has a positive effect on the mechanical characteristics of GP concrete, with an average enhancement of 11% in the compressive strength and 4% improvement in the elastic modulus at 28 days. Replacing sand by the GS at up to 25% develops comparable mechanical properties to those of conventional concrete, with only a 3% and 2% reduction in 28-day compressive strength and elastic modulus, respectively. 50% GS and 35% GGBS develops similar mechanical properties in the waste-based concrete in comparison to the conventional concrete. Incorporating 55% GGBS or 15% FA/40% GGBS reduces concrete water absorption when compared to that of cement-based concrete.
Keywords: Waste Glass; Compressive Strength; Fly Ash; Water Absorption; Elastic Modulus; Blast Furnace Slag